Distribution of Human Immunodeficiency Virus and Human T-Leukemia Virus Co-infection in Bahia, Brazil - Pereira, Felicidade Mota; Santos, Fred Luciano Neves; Silva, Ângelo Antônio Oliveira; Nascimento, Nathan Menezes; Almeida, Maria da Conceição Chagas; Carreiro, Roberto Perez; Galvão-Castro, Bernardo; Rios Grassi, Maria Fernanda (Frontiers in Medicine, 2022)
Human Immunodeficiency Virus (HIV) and Human T-leukemia Virus (HTLV) are retroviruses that share similar routes of transmission. In Brazil, the prevalence of HIV and HTLV varies according to geographic region. The state of Bahia, located in the Northeast region, is considered endemic for both retroviruses. The present study aimed to characterize the frequency of HIV/HTLV coinfection and evaluate the geographic distribution of coinfection throughout the state. This cross-sectional study was conducted at the state’s Central Laboratory of Public Health (LACEN-BA) and included all samples from 2004 to 2013 submitted to serological testing for anti-HIV and anti-HTLV-1/2, screened by chemiluminescence/ELISA and confirmed by Western blot. Infection rates are expressed as the number of infected individuals per 100,000 inhabitants from each municipality. A total of 129,158 samples originating from 358/417 (85.8%) municipalities in Bahia were evaluated. HTLV was detected in 2.4% of the HIV-positive samples (n=42) compared to 0.5% of those with negative HIV serology (n=677) (OR: 4.65; CI: 3.39–6.37). HIV/HTLV coinfection was more frequent in women (69.0%); the median age of coinfected individuals was 47.2 years [interquartile range (IQR): 41.6–55.4 years]. In the 14/417 (3.4%) municipalities where at least one case of HIV/HTLV coinfection was detected, the overall HTLV coinfection rate in HIV-positive samples was 0.25 (range: 0.17-13.84) per 100,000 inhabitants. Most cases of HIV/HTLV-1 coinfection (21/37, 57%) were concentrated in the municipality of Salvador. Isolated instances (one or two cases) of HIV/HTLV-1 coinfection were distributed across municipalities known to be endemic for HTLV infection.